The value of normalization: Group therapy for individuals with brain injury. (19th September 2015) - von Mensenkampff, Barbara; Ward, Marcia; Kelly, Grace; Cadogan, Sam; Fawsit, Feargus; Lowe, Niamh
Abstract: Primary objective : This paper reports on a client-driven therapy group designed to help clients actively process changes and equip them with the psychological skills necessary to facilitate rehabilitation. Research design : This is an exploratory mixed methods research design based in clinical practice. Methods and procedures : This study documents results from five therapy groups, each group consisting of 2-hour sessions over an average of 6 weeks with a review session 6 weeks later. Forty-five clients (13 female, 32 male, average age = 40.54, SD = 11.87) with brain injury attended the group with Headway psychological services, Cork. Clients' pre- and post-measures of functioning were gathered to assess the potential therapeutic benefits. Thematic analysis was used to evaluate the qualitative data. Main outcomes and results : Results illustrate a number of benefits to the participants, including normalizing effects, helping with acceptance, finding a new identity and positive mental health changes. Conclusions : Findings are encouraging and help to validate the effectiveness of group therapy as an intervention tool.